Inclusive hadron yields from D-s(+) decays - Dobbs, S; Metreveli, Z; Seth, K; Tan, B; Tomaradze, A; Libby, J; Martin, L; Powell, A; Thomas, C; Wilkinson, G; Mendez, H; Ge, J; et al. (2009)
We study the inclusive decays of Ds+ mesons, using data collected near the Ds*±Ds peak production energy Ecm=4170MeV by the CLEO-c detector. We report the inclusive yields of Ds+ decays to K+X, K-X, KS0X, π+X, π-X, π0X, ηX, η′X, X, ωX, and f0(980)X, and also decays into pairs of kaons, Ds+→KK̄X. Using these measurements, we obtain an overview of Ds+ decays. © 2009 The American Physical Society.